Breaking Misconceptions: Technology-Integrated MORE Model for Meaningful Learning of Momentum and Impulse - Rizal Adimayuda; Andi Suhandi; Achmad Samsudin; Endi Suhendi; Agus Setiawan; Nuzulira Janeusse Fratiwi (Online Learning In Educational Research (OLER), 2025)
Misconceptions in physics, particularly in topics like momentum and impulse, pose significant barriers to meaningful learning, as students often rely on everyday experiences that contradict scientific principles. Addressing these misconceptions is crucial for improving students’ understanding and application of physics concepts in real-world contexts. This study examines the effectiveness of the Technology-Integrated Modification, Observation, Reflection, and Evaluation (T-MORE) model in addressing misconceptions about momentum and impulse through a convergent parallel mixed-methods design. A total of 22 first-semester undergraduate students participated in this study, receiving instruction incorporating videos, PhET simulations, and AI-assisted reflection tools. Conceptual understanding was measured using the Four-Tier Momentum and Impulse Misconception Diagnostic Test (FT-MIMDT). The McNemar test confirmed a statistically significant improvement, while the Reduction of Misconception Quantity (RMQ) indicated a high reduction in misconceptions. Qualitative analysis revealed changes in students’ misconceptions regarding momentum conservation and impulse-momentum relationships after instruction. These findings confirm the effectiveness of T-MORE in improving conceptual understanding and reducing misconceptions in momentum and impulse. The implementation of T-MORE can be further optimized by incorporating collaborative discussion sessions and adaptive formative assessments to ensure that all students can reconstruct their understanding more comprehensively.